2018
DOI: 10.1186/s13287-018-0813-5
|View full text |Cite
|
Sign up to set email alerts
|

Gas5 is an essential lncRNA regulator for self-renewal and pluripotency of mouse embryonic stem cells and induced pluripotent stem cells

Abstract: BackgroundThe regulatory role of long noncoding RNAs (lncRNAs) have been partially proved in embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs).MethodsIn the current study, we investigated mouse ESC (mESC) self-renewal, differentiation, and proliferation in vitro by knocking down a lncRNA, growth arrest specific 5 (Gas5). A series of related indicators were examined by cell counting kit-8 (CCK-8) assay, quantitative reverse-transcription polymerase chain reaction (qRT-PCR), Western blot, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…Similarly, nutritional deprivation as well as chemotherapy also induced expression of Sox2, Oct4 and Nanog expression 25 . Literature shows that GAS5 is regulated by Sox2 34, 38 . To see if in CD133+ pancreatic cancer cells Sox2 regulated GAS5 mediated growth arrest, we next silenced Sox2 (with siRNA) and studied the expression of GAS5 in CD133 Hi cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, nutritional deprivation as well as chemotherapy also induced expression of Sox2, Oct4 and Nanog expression 25 . Literature shows that GAS5 is regulated by Sox2 34, 38 . To see if in CD133+ pancreatic cancer cells Sox2 regulated GAS5 mediated growth arrest, we next silenced Sox2 (with siRNA) and studied the expression of GAS5 in CD133 Hi cells.…”
Section: Resultsmentioning
confidence: 99%
“…It also mediates cell proliferation by regulating CDK6 activity 17 . Studies have also shown that GAS5 forms a positive feedback network with a number of genes involved in self-renewal like Sox2/Oct4, making this long non-coding RNA (LncRNA) a critical player in induction and maintenance of the “stemness” state in a tumor 34 . GAS5 is further involved in regulation of human embryonic stem cell self-renewal by maintaining NODAL signaling 38 .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA as an important regulator, is involved in multiple functions, including cell growth and pluripotency in mESCs. For example, lncRNA Gas5 is required for the maintenance of mESCs self-renewal and proliferation through interactions with pluripotent transcriptional factors and DNA demethylation regulators (Tu et al, 2018). LncRNA Trincr1 binds TRIM71 to inhibit its SHCBP1 stabilizing activity, and then sensitizes mESCs to depend on Trim71 for rapid proliferation (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These many variants of Gas5 suggest that this gene has a key role in preimplantation embryo development. Previous reports on Gas5 described that it is related to the self-renewal and pluripotency of stem cells [34,35], and it can also act as a competing endogenous RNA (ceRNA) to exert its functions. Furthermore, we found that the expression of AS genes was significantly different in the two-cell stage compared with other stages in preimplantation embryo development (Fig.…”
Section: Difference Of Alternative Splicing Types In Preimplantation mentioning
confidence: 99%